Pola Asuh Anak Usia Dini Ditinjau Dari Latar Belakang Pendidikan Orang Tua - Honits, Dawamatol; Fadli, Adi; Fakhri, Moh. (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Parenting of early childhood aimto find out how parents carry out their roles and responsibilities as parents. In other words, how parents care for their children so that they grow and develop well. If the parenting model usesdifferent pattern, allcannot be separated from the differences of the parents’educational background. This research aimed to find out about a) Parents’educational levelin Batulayar village; b) Parenting style in Batulayar village. The method used in this research was qualitative method. The data collection techniques used were observation, interviews, and documentation. The results of the research showed that the educational levels in Batulayar village, namely Senior High School, Elementary School, and dropout parents from school. The parenting style of parents who graduated from Senior High School applied democratic parenting (authoritative parenting). Meanwhile, parents who graduated from elementary school and parents who dropped out parentsapplied permissive parenting.